2001
DOI: 10.1021/ja003800i
|View full text |Cite
|
Sign up to set email alerts
|

Chain End-Groups Reveal Two States for Palladium-Based Polyketone Catalyst Species

Abstract: Over the past decades several new families of well-defined transition metal-based polymerization catalysts have been discovered. 1 Although these systems are generally referred to as "single-site" catalysts, this seems not to hold in all cases. 2 Deviations of the polydispersity (M w /M n ) of the produced (co)-polymers from the theoretical Flory-Schulz value of 2 have been attributed to polymer precipitation and heterogenization of the catalyst giving rise to "multiple-site" catalysis. 2a,c-f The copolymeriza… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
28
0

Year Published

2001
2001
2017
2017

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(29 citation statements)
references
References 20 publications
(8 reference statements)
1
28
0
Order By: Relevance
“…15 atm and declines at higher pressure. It was suggested that CO impedes coordination of E [31]. The previous experiments have shown that high LVN can be achieved under high total pressure and at low temperature, whereas in order to achieve a high productivity it is necessary to increase the temperature.…”
Section: Influence Of the Pressure Of The Monomersmentioning
confidence: 99%
“…15 atm and declines at higher pressure. It was suggested that CO impedes coordination of E [31]. The previous experiments have shown that high LVN can be achieved under high total pressure and at low temperature, whereas in order to achieve a high productivity it is necessary to increase the temperature.…”
Section: Influence Of the Pressure Of The Monomersmentioning
confidence: 99%
“…Because of growth of the copolymer chain, the solubility of these species gradually decreases and at a certain chain length n, the running catalyst precipitates and becomes heterogeneous. Copolymer chain end-group analysis revealed that this phase transition occurs when n is about 13-20 and is accompanied by a change in the extent to which the two termination reactions, alcoholysis and protonolysis (vide supra), occur while the ratio of chain transfer vs propagation (k t /k p ) increases (115).…”
Section: Nature Of the Catalyst In Polyketone Catalysismentioning
confidence: 99%
“…45:55) deviated from the theoretical value of 1. [7,8] Formation of an excess of ketone end-groups is probably caused by increased partial initiation via a Pd-H species instead of via Pd-OCH 3 . This can occur if initiation via the reactions given in Equations (7) to (10) efficiently competes with those given in Equation (5) and (6).…”
mentioning
confidence: 99%